Intergranular oxidation of 316L stainless steel in the PWR primary water environment. (15th August 2017) - Matthews, R.P.; Knusten, R.D.; Westraadt, J.E.; Couvant, T.
Highlights: Inner Cr-rich oxide growth kinetics is strongly dependent on grain microtexture. This oxide growth is greater at lower temperatures in 290 °C–320 °C range. It is proposed that an epitaxial metal/oxide interface promotes oxide growth. The epitaxial interface may degrade due to differential rates of thermal expansion. Abstract: After exposing AISI 316L stainless steel to the primary water environment across a range of temperatures (290 °C–360 °C) for 1000 h, the oxidation growth of the Cr-rich inner layer was measured. Samples exposed at 290 °C proved to have significantly greater oxide penetration than samples exposed at the higher temperatures. Furthermore, the annealed samples exhibit strong dependence of oxide growth on microtexture. The results suggest that an epitaxial relationship exists between the metal and the Cr-rich oxide, and that this relationship degrades above 290 °C as a result of differential thermal expansion between the oxide and the metal matrix.